2017
DOI: 10.1097/brs.0000000000001728
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Adjacent Segment Disease After Transforaminal Inter-Body Fusion for Degenerative Lumbar Disease

Abstract: Patients with preoperative sagittal imbalance have a statistically significant increased risk of ASD. The risk of ASD incidence was 5.1 times greater in subjects with preoperative PT of more than 22.5°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 25 publications
1
42
1
2
Order By: Relevance
“…The maintenance of spinopelvic alignment is most important for adults with spinal deformity, as this is the primary determinant of life quality after corrective surgery [15] . However, sagittal imbalance reportedly increases the probability of ASD after spinal fusion for LDD [7] . LL is important for maintaining sagittal balance and upright posture.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The maintenance of spinopelvic alignment is most important for adults with spinal deformity, as this is the primary determinant of life quality after corrective surgery [15] . However, sagittal imbalance reportedly increases the probability of ASD after spinal fusion for LDD [7] . LL is important for maintaining sagittal balance and upright posture.…”
Section: Discussionmentioning
confidence: 97%
“…However, ASD may be caused by natural degeneration of the spine. In addition, patient factors such as older age, obesity, pre-existing ASD, facet degeneration, and lumbar amyotrophy may contribute to the development of ASD [6] .Recent studies have shown that the sagittal spinopelvic balance signi cantly affects the clinical therapy of patients with LBP [7,8] . LDD are often associated with spinopelvic imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to relieve clinical symptoms without considering the problem of fixed segment movement. Long-term follow-up reveals adjacent segment ROM increased to compensate for the lost ROM of the fixed segment, resulting in ASD [13][14][15][29][30][31][32][33]. Following improved knowledge of lumbar motion function, surgeons now consider how to treat lumbar degenerative disease while maintaining ROM, and dynamic stabilization has been developed and accepted.…”
Section: Discussionmentioning
confidence: 99%
“…There are several theoretical advantages of fusion techniques, such as restoration of disc height(DH), correction of sagittal spinal balance, and decompression of the neural foramina. [10][11][12] Recently, oblique lumbar interbody fusion (OLIF) is one of the emerging minimally invasive techniques which has progressively been used. The advantages of this minimally invasive technique is avoiding injury to the paraspinal muscles, psoas muscle, and lumbar plexus, owing to it reach the intervertebral space by the retroperitoneal channel directly.…”
Section: Introductionmentioning
confidence: 99%